EVALUASI KEGIATAN USAHA MIKRO DAN KECIL (UMK) DALAM PENGELOLAAN LIMBAH PADAT MENJADI PRODUK YANG MENGUNTUNGKAN (PROFIT ORIENTED) MELALUI PENERAPAN DEBT FOR NATURE SWAP - Lutfiah Lutfiah (Program Studi Manajemen Lingkungan, 2014)
The research supposed to got on accurate answer in relation to the evaluation of Micro and Small Enterprises (MSEs) effort of waste to profit oriented products on management and the government’s contribution by Debt for Nature Swap (DNS). The analysis quantitative of plastic recycle’s management in Bekasi. The sample of research used random sampling technique as much as 50 people. The data analysis needs to do with distributing questioner and interview. the research to do with descriptive quantitative method close to quantitative analysis. It is to facilitate observation to result’s analysis, data of result’s analysis provide histogram and hypothesis experiment to knows the variable of evaluation of micro and small enterprises (MSEs) effort waste to profit oriented products on management and the government’s contribution by debt for nature swap (DNS). based on the result of the research will get’s: (1) it would be able the evaluation of micro and small enterprises (MSEs) effort of waste to profit oriented products on management by debt for nature swap (DNS), and (2) it would be able between the government’s contribution by debt for nature swap.